Potential of Ideonella sakaiensis bacteria in Degrading Plastic Waste Type Polyethylene Terephthalate - Sherina Juliana; Mia Parhusip; Argoby Simanullang; Elisabeth Tita; Wahyu Irawati (Jurnal Biologi Tropis, 2022)
Polyethylene terephathalate (PET) is a type of plastic content that is commonly is difficult to degrade so that it has an impact on global environmental problems. Plastic waste pollution needs to be overcome by using environmentally friendly methods to accelerate the PET plastic biodegradation process. Biodegradation is the use of microorganism activity to decompose plastic compounds so as to reduce the volume of waste. Ideonella sakaiensis is a bacterium that produces PETase enzymes that play a role in degrading PET. This literature review aims to determine the potential of Ideonella sakaiensis encoding the PETase gene in degrading polyethylene terephathalate plastic waste by discussing three focus studies, namely: 1) the potential of Ideonella sakaiensis, 2) the characteristics of polyethylene terephathalate plastic waste, 3) the relationship between the PETase coding gene and the degradation of polyethylene plastic waste terephathalate. Biodegradation of plastic waste Polyethylene terephathalate using Ideonella sakaiensis which has the potential to degrade PET faster with the PETase enzyme. The biodegradation mechanism carried out involves the process of transforming the PETase coding gene from I. sakaiensis to Escherichia coli bacteria influenced by pH and the effectiveness of the PETase enzyme work until the use of harvested products interacts with Polyethylene terephathalate plastic waste, which decomposes plastic waste.ÃÂ